Development and characterization of polyclonal antibody against human kappa light chain in rabbit - Esparvarinha, Mojgan (Vet Res Forum, 2019)
Polyclonal antibodies against kappa light chain are used to diagnose diseases producing free light chain. The kappa and lambda light chains are products of immunoglobulin synthesis and released into the circulation in minor amounts such as serum, cerebrospinal fluid, urine and synovial fluid in normal condition. The purpose of this study was the production and purification of polyclonal immunoglobulin G (IgG) against human kappa light chains. In this study, early human IgG was purified by ion-exchange chromatography, reduced with Dithiothreitol and heavy and light chains were separated with size-exclusion chromatography. Afterward, affinity chromatography with protein L Sepharose at pH 2.00 was displayed to be a dominant condition for the separation and purification of the kappa light chain of immunoglobulins from human serum. Eventually, the rabbit was immunized by human kappa light chains. The rabbit IgG was purified and labeled with horseradish peroxidase (HRP). Direct enzyme-linked immunosorbent assay was planned to determine the titer of HRP conjugated rabbit IgG against the human kappa light chain. The optimum titer of anti-kappa IgG was 1:16000. At the result, purified polyclonal anti-kappa is useful tool in biomedical and biochemical researches and diagnostic kits.